IL1RA inhibits the progression of oral squamous cell carcinoma by mediating type Ⅰ interferon response - Yujie Ding; Yufei Shan; Jiaqi Gu; Jie Yi; Zhida Sun (Translational Oncology)
Interleukin-1 receptor antagonist (IL1RA) is an anti-inflammatory and anti-tumor protein, and a member of the Interleukin-1 (IL-1) family. Our previous finding showed that IL1RA is a tumor marker for oral squamous cell carcinoma (OSCC), but the exact mechanism is unknown. The present study aims to investigate the biological role of IL1RA in the progression of OSCC in vitro and in vivo and the underlying molecular mechanism. IL1RA was lowly expressed in OSCC specimens and cells, and its overexpression significantly inhibited the proliferation and migration of OSCC cell lines CAL27 and HN6. In nude mice bearing OSCC xenografts, in vivo overexpression of IL1RA significantly reduced tumor growth without influencing epithelial-mesenchymal transition (EMT). Differentially expressed genes (DEGs) in OSCC cells overexpressing IL1RA were identified by RNA sequencing (RNA-seq), and they were significantly enriched in cancer-associated signaling pathways like type I interferon response. IL1RA upregulated interferon alpha (IFNA) and interferon beta (IFNB), known for their anti-cancer properties, in OSCC cells and specimens. In conclusion, IL1RA inhibits the malignant progression of OSCC by mediating the type I interferon response.